Some reflections on monetary policy, in the light of the Radcliffe report - Franks, Oliver Shewell (Bombay ; New York : Asia Pub. House, 1960)
This contains the lectures presented at the first Dorab Tata foundation. The lectures were devoted on international monetary policy, balance of payment and monetary reserves.
usc 11/10/18
Loans
Keywords: Currency question; Monetary policy; Great Britain